1985
DOI: 10.1177/0306624x8502900209
|View full text |Cite
|
Sign up to set email alerts
|

Girls Who Kill

Abstract: Clinical case histories of two juvenile girl murderers are presented to explore possible causative psychodynamics and assess their congruence with a large series of boys who committed homicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…The literature on juvenile murderers has consisted predominantly of studies with small sample sizes of 20 cases or less (see, for example, Bailey, 1996;Britvic, Urlic, & Definis-Gojanovic, 2006;Hughes, Zagar, Busch, Grove, & Arbit, 2009;Kashani, Darby, Allan, Hartke, & Reid, 1997) and case studies (see, for example, Cornell, 1989;Davis & Dutcher, 2002;Heide & McCurdy, 2010;Malmquist, 2010;Mouridsen & Tolstrup, 1988). Several publications reported case studies of girls who killed (see, for example, Benedek & Cornell, 1989a;Ewing, 1990;Gardiner, 1985;Heide, 1992Heide, , 1999Heide & Solomon, 2009;McCarthy, 1978;Medlicott, 1955;Mukaddes & Topcu, 2006;Myers, 2004;Reinhardt,1970;Russell, 1986).…”
Section: Juvenile Homicide Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The literature on juvenile murderers has consisted predominantly of studies with small sample sizes of 20 cases or less (see, for example, Bailey, 1996;Britvic, Urlic, & Definis-Gojanovic, 2006;Hughes, Zagar, Busch, Grove, & Arbit, 2009;Kashani, Darby, Allan, Hartke, & Reid, 1997) and case studies (see, for example, Cornell, 1989;Davis & Dutcher, 2002;Heide & McCurdy, 2010;Malmquist, 2010;Mouridsen & Tolstrup, 1988). Several publications reported case studies of girls who killed (see, for example, Benedek & Cornell, 1989a;Ewing, 1990;Gardiner, 1985;Heide, 1992Heide, , 1999Heide & Solomon, 2009;McCarthy, 1978;Medlicott, 1955;Mukaddes & Topcu, 2006;Myers, 2004;Reinhardt,1970;Russell, 1986).…”
Section: Juvenile Homicide Literaturementioning
confidence: 99%
“…Research studies of homicide by juveniles have been primarily clinical in focus. They have focused on victim characteristics, including interfamilial victims and parricide (Corder, Ball, Haizlip, Rollins, & Beaumont, 1976;Duncan & Duncan, 1971;Evans, McGovern-Kondik, & Peric, 2005;Ewing, 1990;Heide, 1992Heide, , 1994Kalogerakis, 1971;Russell, 1986;Sargent, 1964;Wertham, 1941;Zenoff & Zeints, 1979). These studies have often identified mental health disorders (Cornell, Miller, & Benedek, 1988;Labelle, Bradford, Bourget, Jones, & Carmichael, 1991;Lewis et al, 1985;Myers & Scott, 1998;Myers, Scott, Burgess, & Burgess, 1995), substance abuse (Bailey, 1996;Cornell, Benedek, & Benedek, 1987;Fenderich, Mackesy-Amiti, Goldstein, Spunt, & Brownstein, 1995;Myers & Scott, 1998), poorer executive functioning and lower social maturity (R. J. , and severe family dysfunction and family pathology in the backgrounds of these killers (Busch, Zagar, Hughes, Arbit, & Russell, 1990;Crespi & Rigazio-DiGilio, 1996;Hill-Smith, Hugo, Hughes, Fonagy, & Hartman, 2002;R.…”
Section: Juvenile Homicide Literaturementioning
confidence: 99%
“…A few publications report case studies of girls who have murdered (see, for e.g., Ewing, 1990;Gardiner, 1985;Heide, 1992;McCarthy, 1978;Medlicott, 1955;Russell, 1986). These studies reveal that girls are more likely than boys to kill family members and to use accomplices to effect these murders.…”
Section: Girls Who Killmentioning
confidence: 99%
“…Several researchers have found significant neurological impairment or abnormalities among young killers (see, e.g., Bailey, 1996a;Bender, 1959;Busch et al, 1990;Lewis et al, 1985;Lewis, Lovely, et al, 1988;Michaels, 1961;Myers, 1994;Myers et al, 1995;Woods, 1961;Zagar, Arbit, Sylvies, Busch, & Hughes, 1990), particularly those on death row (Lewis, Pincus, et al, 1988). Others maintain that neurological difficulties are absent or rare among the juvenile murderers assessed in their studies (see, e.g., Dolan & Smith, 2001;Hellsten & Katila, 1965;Labelle et al, 1991;Petti & Davidman, 1981;Russell, 1986;Scherl & Mack, 1966;Walshe-Brennan, 1974.…”
Section: Neurological Impairment and Youth Homicidementioning
confidence: 99%
See 1 more Smart Citation